Implementation of the Teaching Assistance Program at SMP Negeri 1 Bawolato : A Study of the Experiences of Education Students (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the implementation of the Teaching Assistance Program as part of the Merdeka Belajar Kampus Merdeka (MBKM) policy, focusing on the experiences of education students at SMP Negeri 1 Bawolato, a rural secondary school in North Nias, Indonesia. The problem addressed in this study is the limited empirical documentation of MBKM implementation in remote educational settings with constrained infrastructure and unique pedagogical cultures. The primary objective is to investigate how teaching assistance contributes to the development of pedagogical, social, and adaptive competencies among student-teachers. A qualitative descriptive case study approach was applied, involving participatory observation, in-depth interviews, and document analysis. Thematic analysis was used to interpret the data. The findings indicate that the program significantly enhances students' pedagogical skills, including lesson planning, classroom management, and reflective teaching. Collaboration with mentor teachers and contextual adaptation emerged as crucial factors in successful implementation. The program also had a positive impact on student engagement in classrooms. This study contributes to the literature by highlighting the role of experiential learning in bridging theory and practice within teacher education, particularly in underrepresented rural contexts. It also offers recommendations for policy design and curriculum development in teacher training programs. The study concludes that meaningful field experiences, supported by collaborative mentorship and reflective practice, are key to producing competent and adaptive future educators.